Analysis of Scientific Researches in the Field of Vocational Training of Ukraine (the Second Half of the Twentieth Century) - Olena Danylova (Pedagogical Discourse, 2013)
This article deals with the nature and the theoretical analysis of the numbers of scientists researches of the Soviet period and the present as for the development of vocational training in Ukraine of the second half of the twentieth century. The main feature of the history of vocational training in the Soviet era was that the problem was seen through the prism of party historiography. With the proclamation of the independence of Ukraine, the situation in historical researches has changed, namely trend of rethinking of key events and problems without affecting of Marxist-Leninist ideology has appeared. The basic questions on which the researchers were working with the purpose of using of their achievements in modern conditions and using in searching the new ways of modernization of training system of skilled workers are explained.